The Situation of Digitization in the Hungarian Food Processing Industry - Debrenti, Attila Sándor (International Journal of Engineering and Management Sciences, 2020)
Thanks to various technologies, such as nanotechnology, the next decades will completely transform the individual production processes and sectors. With the rapid advancement of information technology, the digitalization and automation of industrial processes pose new challenges for food business operators. Hungarian food companies will be able to keep up with their competitors and be the winners for the next decades if they can successfully adopt these technologies. However, this requires a strong focus on digitization, digital strategy, and directing investment, technology change and R&D activities in this direction. Digitization is one of the decisive directions of the future, which is why I felt it essential to study the level of digitization of Hungarian food companies, IT infrastructure and Internet usage, the use, and role of enterprise management systems, decision support and business analysis tools, and business readiness, Industry 4.0 technology change. Based on the 205 evaluable responses to the questionnaire, it can be said that only a tiny proportion of Hungarian food companies have a digital strategy and only a few have digital transformation.